Jejak Digital dan Amal Jariyah: Perspektif Al-Qur’an Tentang Aktivitas Online - Febrina Herdian; Hania Alfi Naila Putri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This article examines the concept of digital footprints on TikTok and Instagram platforms as modern deed records from the Al Qur'an perspective, exploring the opportunities for ongoing charity versus ongoing sin including the increasingly troubling phenomenon of online gambling (judol), and the urgency of Islamic digital ethics and literacy for contemporary social media users. The research method used is library research with a descriptive-analytical qualitative approach, integrating relevant Al Qur'anic verses such as QS. Qaf: 18 about the recording angels Raqib and Atid, QS. Az-Zalzalah: 7-8 regarding accountability of deeds, and QS. Al-Baqarah: 219 about the principle of balancing benefits and harms, supplemented by related hadiths and various contemporary literature sources. The research findings indicate that digital traces in the form of videos, likes, comments, and GPS location data resemble the function of angels tasked with recording every human action. Social media platforms have the potential to become virtual da'wah mediums for spreading useful knowledge widely and continuously, yet they are also vulnerable to negative content that creates perpetual sins through the For You Page algorithm which reinforces exposure based on user preferences. The application of qaulan sadida (honest communication), tabayyun (fact verification), and amar ma'ruf nahi munkar can minimize these risks. This study's conclusion emphasizes that the Al Qur'an can serve as the main guide in maintaining the balance of benefits and harms in the Digital Era. Recommendations include the importance of Islamic digital literacy training in educational institutions and mosques, implementation of judol prevention regulations, and further empirical research needed to explore broader impacts on social media user behavior in Indonesia.